PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI ARITMATIKA SOSIAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMPN 2 ENDE SELATAN - Imaculata Ngadha (Program Studi Pendidikan Matematika, 2019)
The problem in this research is that teacher-oriented learning. While student learning activities that are often done are listening and taking notes. Students become embarrassed to ask the teacher if there are difficulties in solving and solving the problems given. Therefore, one of the learning models that can make students active and exchange opinions in solving mathematical problems. The appropriate learning model is type cooperative learning (TAI), through this learning students can facilitate active in individuals or groups, so as to improve student learning outcomes. This type of research is classroom action research (CAR), in this study there are two cycles where each cycle consists of 4 stages, namely the planning stage, the stage of implementing the action, the stage of observation and reflection. The subjects of this study were 29 grade VII students of SMPN 2 South Ende. Data collection techniques used are observation, testing and documentation. The results of the study were obtained before using cooperative learning type TAI, the percentage of completeness student learning outcomes 37.93%. After using the cooperative learning model TAI in the first cycle of action has increased with the percentage of completeness of learning outcomes by 44.82%, and continued in the second cycle has increased learning outcomes to reach 100%. This shows that the TAI type of cooperative learning model can improve the learning outcomes of social arithmetic material in grade VII students of SMPN 2 Ende Selatan.